KEGIATAN BERBASIS PENDIDIKAN DI SAUNG PINTAR DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK SEBAGAI KHIDMAH KEPADA MASYARAKAT - Saepulloh Saepulloh (LPPM STAI Darul Falah, 2023)
The community service program aims: 1) to improve the learning achievement of school-aged children; 2) to increase school-aged children's learning motivation; 3) to help parents pay more attention to their children in studying in Sukamulya Village and activities carried out in Saung Pintar. A form of community service activity is carried out by providing learning assistance in tutoring. The subject of service is school age children. Implementation of activities goes through several stages, namely planning, observation, determining technical implementation, program implementation and evaluation. The results of community service obtained have been successful in: 1) improving the learning achievement abilities of school-age children; 2) increase the learning motivation of school-aged children; 3) help parents pay more attention to their children in studying in Sukamulya Village. Community service in the field of education is carried out by Field Supervisors and assisted by students participating in Real Work Lectures (KKN). After learning assistance was held, children who were initially not interested in learning assistance and preferred playing, have now become more interested in learning assistance. Based on the community service activities that have been carried out, several things can be concluded, namely: 1) to increase the learning achievement and motivation of school-age children in learning assistance is to organize children's study schedules, provide social and emotional stimulation for children; 2) to increase the learning motivation of school age children in learning assistance is to use interesting learning methods and give awards or prizes to the children; 3) to help parents pay more attention to their children in learning and build two-way communication with their children, become companions when studying at Saung Pintar, and supervise children's daily activities.